Waqf in Transition: Tracing Local Institutional Change during the British Mandate in Palestine - Murray, Zachary (AUC Knowledge Fountain, 2022)
The British Mandate’s actions of state-building in Palestine were informed by a Zionist-Western modernist envisioned past of Palestine. This state-building ideology was embedded within much of the bureaucracy of the Mandate’s system and infringed on numerous Palestinian institutions such as Waqf. Waqf was disenfranchised in particular through the implementation of urban development programs, like town planning and archaeological regimes, which sought to support the British-Zionist recasting of Palestine. This thesis aims to show how the British’s ideology of Palestine informed the Mandate’s internal polices and actions which infringed on the rights of waqf. This was done through two axes of inquiry. The first axis analyses the role of British programs and institutions, and I take the example of town planning policies as a site for analysis. I demonstrate that town planning designed by appointed British town planners understood Palestine through a Zionist-Christian lens. This ideological lens was a presumption of the Mandate powers that Palestine was by definition the historical site of the Hebrew/Israeli peoples and thus the proper site of a nation-state building effort for a modern Zionist state. This state-building effort was legitimized within the British official mind in Palestine and more specifically by the Mandate’s Department of Archaeology. The crafting of a historical claim of a national-mythology through collecting ancient artifacts were used by the Department of Archaeology to give credence to the political efforts of the British and Zionist state-building efforts as a means of grounding their modernization mythology of Palestine ought to be the future home of the Jews. This placed the proper procedure of nationalization of the modern state on an ancient historical foundation in which saw that only through the re-injection of that ancient historical foundation a modern state in Palestine could emerge. The second axis of inquiry looks at the specific case study of Jerusalem and selects two episodes of contention. The two episodes show how the state formation process of the Mandate privileged the Zionist-Christian mythology of Palestine over the Palestinian political and social experience prior to the Mandate. The first site of contention is where the Department of Archaeology and the Supreme Muslim Council battled over the defining of the White Minaret in Ramla Palestine. This case shows the privileging of the Zionist-Christian envisioning of the built environment over the legal waqf rights of the Minaret. The second site of contention is situated in the walls of Jerusalem. This site shows how Town Planning schemes, and the Department of Archaeology worked in tandem to restore the city as a Jewish site through the removal of Palestinian built environments on and near the wall. This, again, privileged a Zionist-Christian understanding of Jerusalem over the lived space of Palestinians within Jerusalem.